EXPLORING MANAGEMENT THEORIES IN REDEFINING NEW WOMANHOOD: A STUDY OF SHASHI DESHPANDE’S ‘THE DARK HOLDS NO TERRORS’ (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This study examined Shashi Deshpande's novel, "The Dark Holds No Terrors," and its portrayal of the psychological and cultural experiences of middle-class Indian women. It highlighted the novel's focus on the values and significance of "New Womanhood" and the female oppression within patriarchal family structures. The study aims to highlight Deshpande's concern for women in India and how her novel not only presents the traumatic experiences of the protagonist but also inspires them to gain, independence from patriarchal constraints and self-revelation. The study investigated the importance of understanding and addressing the challenges faced by educated women, employed a descriptive research design, utilizing both primary and secondary sources, to delve into the significance of NEW WOMANHOOD, with the scientific approach of psychological and cultural gynocentric theories to Shashi Deshpande's novel, considering Maslow's Hierarchy of human needs for self-actualization and discussed the protagonist's self-discovery and identity phase through new womanhood in the novel's context. The study revealed that women's positive attitude substitute is crucial for achieving position and boosting themselves in patriarchal society. In accordance with Shashi Deshpande’s dedication in addressing women psychological trauma highlighted that women need to help themselves to establish a firm footing in family, society and empowering themselves to overcome life's challenges. It also suggested future research on Deshpande's treatment of feminism in various aspects in her novels and short stories.